profile
Опубликовано 1 год назад по предмету Алгебра от Регинчик1999

(2х-0,1)+(3х-5)=7
(х-0,2)+(4х-3)=8
(х+0,5)-(2х-3)=9

  1. Ответ
    Ответ дан ФАИНА1984
    (2х-0,1)+(3х-5)=7
    2х-0.1+3х-5=7
    5х=7+0.1+5
    5х=12.1
    х=12.1:5
    х=2.42

    (х-0,2)+(4х-3)=8
    х-0.2+4х-3=8
    5х=8+0.2+3
    5х=11.1
    х=11.2:5
    х=2.24

    (х+0,5)-(2х-3)=9
    х+0.5-2х+3=9
    -х=9-0.5-3
    -х=5.5
    х=-5.5
  2. Ответ
    Ответ дан AVfomicheva
    (2х-0,1)+(3х-5)=7                     
     (х-0,2)+(4х-3)=8                        2х-0,1+3х-5=7                                   
    2х+3х=0,1+7                            2х+3х-0,1-5=7
    5х=7,1                                      5х-5,1=7
    х=7,1: 5                                      5х=7+5,1
    х=1,42                                         5х=12,1
                                                        х=12,1:5
                                                         х=2,42

Самые новые вопросы